The impact of digital transformation strategy on the performance of commercial banks: Evidence from an emerging economy - Bui, Trung Huy; Duong, Yen Thi (The Economics and Finance Letters, 2025)
This study examines the impact of digital transformation strategies on the financial performance of commercial banks in Vietnam, an emerging economy with significant digital growth potential. Using a sample of 18 Vietnamese banks from 2015 to 2022, the study employs the Generalized Method of Moments (GMM) to address endogeneity concerns and provide robust estimates of the relationship between digital transformation and bank performance. The digital transformation strategy variable is measured through a text analysis of bank annual reports. Our findings reveal that banks integrating digital transformation into their strategies exhibit improved financial performance, with a more pronounced effect among banks that comply with Basel II standards. The study’s insights have important implications for both policymakers and bank managers in emerging markets. Policymakers are encouraged to support digital transformation as a pathway to enhanced financial sector growth, while bank managers are advised to treat it as a strategic priority to unlock efficiency and competitive advantages. Moreover, the results emphasize the value of strong regulatory compliance in maximizing the benefits of digital transformation strategies in the banking sector.